The Importance of Loosely Systematized Game Phases in Sports: The Case of Attack Coverage Systems in High-Level Women's Volleyball - Lorenzo Laporta; Pantelis Nikolaidis; Luke Thomas; José Afonso (Montenegrin Sports Academy, 2015)
Change is ubiquitous, but its degree and rate often affords detection of emerging patterns and establishing behavioral dynamics based on expected regularities. Match analysis capitalizes on such regularities, capturing information relevant for enhancing structure and reducing improvisation to a minimum. However, what if a game phase is only loosely regular, defying pattern systematization? Is it still possible to unfold principles of behavior capable of abstracting over-arching patterns? Our research focused on analysis of complex IV (KIV) or attack coverage in volleyball. Fourteen matches from the 2013 Volleyball Women's World Grand Champions Cup were analyzed. Results showed the occurrence of KIV corresponded to fewer than 5% of the total number of actions, and plays where a team successfully conquered a point after attack coverage was circa 1%, meaning this game complex will only make a difference in balanced matches. Overall, twenty-nine attack coverage structures emerged, denoting very high organizational variability. Attack coverage therefore provides an example of principle-based and not structured-based game phase. Associative analysis showed that quick attack tempos constrain the emergence of more complex attack coverage structures. The search for principle-based instead of structure-based game phases may provide useful insights for comprehension of game dynamics and for informing training processes.